Environmental Effects of China's Nuclear Energy within the Framework of Environmental Kuznets Curve and Pollution Haven Hypothesis - Raihan, Asif; Ridwan, Mohammad; Tanchangya, Tipon; Rahman, Junaid; Ahmad, Shakil (Journal of Environmental and Energy Economics, 2023)
This study investigates the environmental sway of China's nuclear energy use in the perspective of the Environmental Kuznets Curve (EKC) and Pollution Haven Hypothesis (PHH) by using the time series data from 1993 to 2022. The study used an autoregressive distributed lag (ARDL) simulating method. One of the limitations of the study is the short range of the data although the ARDL method perfectly applicable for the dataset with a short range. The findings of empirical research support that the PHH does not apply to China, meaning that foreign direct investment significantly impacts environmental results. Moreover, empirical findings confirmed the helpful impact of nuclear energy in reducing pollutants. Furthermore, the outcome confirms the EKC theory in the Chinese context, suggesting that increasing economic expansion may decrease emission levels in the future. Higher economic growth and increased foreign investment in nuclear energy generation are expected to improve environmental excellence by decreasing carbon emissions.